2018
DOI: 10.1021/acs.orglett.7b03948
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Reactivity and Site-Selectivity in Hydrogen Atom Transfer from Amino Acid C–H Bonds via Deprotonation

Abstract: A kinetic study on the reactions of the cumyloxyl radical (CumO) with N-Boc-protected amino acids in the presence of the strong organic base DBU has been carried out. COH deprotonation increases the electron density at the α-C-H bonds activating these bonds toward HAT to the electrophilic CumO strongly influencing the intramolecular selectivity. The implications of these results are discussed in the framework of HAT-based aliphatic C-H bond functionalization of amino acids and peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The selectivity pattern observed with the 1/H 2 O 2 system resembles that of the cumyloxyl radical (CumO˙) where exclusive HAT from α-C–H bond with Ala and a competition between side-chain vs. Cα–H bond cleavage for N -AcLeuOMe (4) were observed. 16 However, no HAT reaction from the tertiary β-C-H bond of N -AcValOMe (3) has been observed with CumO˙, thus indicating that our system is less sensitive to steric effects in the HAT process.…”
Section: Resultsmentioning
confidence: 85%
“…The selectivity pattern observed with the 1/H 2 O 2 system resembles that of the cumyloxyl radical (CumO˙) where exclusive HAT from α-C–H bond with Ala and a competition between side-chain vs. Cα–H bond cleavage for N -AcLeuOMe (4) were observed. 16 However, no HAT reaction from the tertiary β-C-H bond of N -AcValOMe (3) has been observed with CumO˙, thus indicating that our system is less sensitive to steric effects in the HAT process.…”
Section: Resultsmentioning
confidence: 85%
“…Along similar lines,t ime-resolved kinetic studies in acetonitrile solution on the reactions of the cumyloxyl radical (PhC(CH 3 ) 2 OC,C umOC)w ith N-Boc-protected amino acids bearing aliphatic side chains have shown that the addition of the strong organic base 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) increases the second-order rate constants for HAT, with kinetic effects,q uantified on the basis of the rate constant ratio k H (DBU)/k H ,w hich can exceed one order of magnitude (Table 1). [39] This behavior has been explained in terms of the deprotonation of CO 2 Hb yD BU that, by increasing the electron density at the a-C À Hb onds,a ctivates these bonds toward HATt ot he electrophilic CumOC,a sd escribed in Scheme 2, path b (XH = CO 2 H). Thel ower k H (DBU)/k H ratios measured for N-BocLeuOH, N-BocProOH, and N-BocPheOH compared to N-BocGlyOH, N-BocAlaOH, and N-BocValOH reflect competitive HATfrom side-chain CÀH bonds of the former substrates, [40] which indicates that CO 2 H deprotonation strongly influences the intramolecular selectivity with these substrates (Scheme 12).…”
Section: Acid-base Interactionsmentioning
confidence: 99%
“…, CumO . ) with N ‐Boc‐protected amino acids bearing aliphatic side chains have shown that the addition of the strong organic base 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) increases the second‐order rate constants for HAT, with kinetic effects, quantified on the basis of the rate constant ratio k H (DBU)/ k H , which can exceed one order of magnitude (Table ) …”
Section: C−h Bond Activationmentioning
confidence: 99%
“…mit N ‐Boc‐geschützten Aminosäuren, die aliphatische Seitenketten aufweisen, dass die Zugabe der starken organischen Base 1,8‐Diazabicyclo[5.4.0]undec‐7‐en (DBU) die Geschwindigkeitskonstanten zweiter Ordnung für den HAT erhöht. Das für die Quantifizierung der kinetischen Effekte ermittelte Verhältnis der Geschwindigkeitskonstanten k H (DBU)/ k H kann sich dabei um eine Größenordnung unterscheiden (Tabelle ) …”
Section: C‐h‐bindungsaktivierungunclassified